0811 The Association between Habitual Midday Napping and Impaired Fasting Glucose in Adolescents. (27th April 2018) - Ji, X; Saylor, J; Liu, J
Abstract: Introduction: Midday napping is a common sleep behavior among adolescents, especially in countries who have siesta cultures such as China. Research among adults illustrates the association between napping and impaired glucose metabolism, thus increased risk of diabetes. However, there is limited evidence on the adolescent population. The purpose of this study was to investigate the association between habitual midday napping and impaired fasting glucose (IFG) among adolescents in China. Methods: The sample was comprised of 638 early adolescents (12.01 ± 0.38 years old) who self-report good health status from Jintan, China. Midday napping frequency and duration were measured using the Youth Self-Report Sleep Questionnaire. Fasting plasma glucose concentrations were dichotomized into normal (<5.5mmol/L) and impaired (≥5.6mmol/L) glucose levels. Logistic regression was used to examine the nap-glucose relationship, while controlling for age, gender identity, parental education, home residence, BMI, plasma cholesterol concentrations, nighttime sleep duration and quality. Results: Of the participants, 391(62.66%) napped more than 3 times per week and 422 (68.28%) reported nap durations of greater than 30 minutes on average. One-hundred participants (15.92%) had IFG. After adjusting for covariates, non-habitual nappers (≤2 d/week) (OR=1.11, p=0.02) and moderate nappers (3–4 d/week) (OR=1.38, p=0.04) were associated with an increased likelihood of IFG relative to frequent nappers (5–7 d/week). There was a U-shaped association between nap duration and IFG. Compared with the never-napped group, adolescents who took very short naps (≤15 minutes) demonstrated a decreased likelihood of IFG (OR=0.64, p=0.04). There were no predictive effects of short (16–30 minutes) and moderate nap-lengths (31–60 minutes) versus a never-napped condition (p's>0.05), followed by a significantly increased likelihood of IFG at long naps over 60 minutes (OR=1.40, p=0.01). Conclusion: This study suggests that routine nappers are less likely to have IFG, thus decreasing diabetes risk. However, there is a dose-response relationship between nap length and IFG, with only naps ≤15 minutes were associated with a decreased likelihood of IFG. This study represents an initial step to inform optimal sleep behaviors among adolescents in diabetes prevention and management. Support (If Any): R01-ES018858, K01-ES015877, K02-ES019878.